Thermodynamic modelling of liquid-vapour equilibrium and thermophysical properties of molten Pb–Bi systems. (2nd January 2017) - Barbin, Nikolay; Terentiev, Dmitry; Alexeev, Sergey; Barbina, Tatyana
ABSTRACT: A lead–bismuth alloy is an advanced coolant for nuclear power plants. The study of this alloy is of current importance. However, performing high-temperature experiments involves many problems. In this work, to study evaporation of a lead–bismuth alloy in the presence of intermetallic compounds in the condensed phase and dimers and trimers of metals in the vapour phase, a method of thermodynamic modelling was used. The investigations were carried out at temperatures from 400 to 3000 K with the lead content from 0.1 to 0.9 weight fractions in the lead–bismuth alloy. In the method of thermodynamic modelling a software package TERRA and a model of an ideal solution of interaction products were applied. Concentration and temperature dependencies of the content of components in the melt and in the gaseous phase over the melt were calculated. Temperatures, enthalpies, entropies of the melt–vapour transition and various thermophysical properties were defined.